Central nervous system paracoccidioidomycosis. report of a case successfully treated with itraconazol (2000)
ABSTRACT: Paracoccidioidomycosis (PCM) is a primary pulmonary infection that often disseminates to other organs and systems. Involvement of the central nervous system (CNS) is rare and due to the fact that both clinical alertness and establishment of the diagnosis are delayed, the disease progresses causing serious problems. We report here a case of neuroparacoccidioidomycosis (NPCM), observed in a 55 year-old male, who consulted due to neurological symptoms (left hemiparesis, paresthesias, right palpebral ptosis, headache, vomiting and tonic clonic seizures) of a month duration. Upon physical examination, an ulcerated granulomatous lesion was observed in the abdomen. To confirm the diagnosis a stereotactic biopsy was taken; additionally, mycological tests from the ulcerated lesion and a bronchoalveolar lavage were performed. In the latter specimens, P. brasiliensis yeast cells were visualized and later on, the brain biopsy revealed the presence of the fungus. Treatment with itraconazole (ITZ) was initiated but clinical improvement was unremarkable; due to the fact that the patient was taking sodium valproate for seizure control, drug interactions were suspected and confirmed by absence of ITZ plasma levels. The latter medication was changed to clonazepam and after several weeks, clinical improvement began to be noticed and was accompanied by diminishing P. brasiliensis antigen and antibody titers. In the PCM endemic areas, CNS involvement should be considered more often and the efficacy of itraconazole therapy should also be taken into consideration.